2019
DOI: 10.3139/120.111390
|View full text |Cite
|
Sign up to set email alerts
|

Phase evolution of surface-modified Incoloy 825 superalloy using pack aluminization

Abstract: The objective of the study is to investigate the phase evolution of the aluminized surface of iron-concentrated nickel-based superalloys. Aluminization is carried out via pack cementation at constant temperature of 900 °C at three processing times of 1, 2.25 and 4 h. Backscattered images and X-ray diffractions are used for phase identification. Small incident angle X-ray diffraction applied on the surface and subjected to repetitive polishing elucidate a formation sequence of iron aluminides. The overall thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…It was found that the simultaneous addition of 1% cerium and 6% silicon led to the formation of Ce 1 Si 6 , which limits the oxygen diffusion, promotes the growth of the continuous Al 2 O 3 layer, and further enhances the hot-oxidation resistance of the coating. A similar improvement in the hot-temperature corrosion resistance was reported for aluminized Incoloy 825 [12], Inconel 625 [13], and Inconel 600 [14]. One should mention that PC could also significantly improve the mechanical behavior of the protected substrate.…”
Section: Pack Cementation (Pc) and Above The Pack/vapor-phase Alumini...supporting
confidence: 73%
See 2 more Smart Citations
“…It was found that the simultaneous addition of 1% cerium and 6% silicon led to the formation of Ce 1 Si 6 , which limits the oxygen diffusion, promotes the growth of the continuous Al 2 O 3 layer, and further enhances the hot-oxidation resistance of the coating. A similar improvement in the hot-temperature corrosion resistance was reported for aluminized Incoloy 825 [12], Inconel 625 [13], and Inconel 600 [14]. One should mention that PC could also significantly improve the mechanical behavior of the protected substrate.…”
Section: Pack Cementation (Pc) and Above The Pack/vapor-phase Alumini...supporting
confidence: 73%
“…Although all of them were used to deposit NiAl coatings to improve some functional properties of the base materials, one can expose different approaches leading to the same findings. It could be noticed that PC methods are mainly used to deposit pure NiAl or β-NiAl coatings [6,7,[12][13][14][15][16][17]23,24]. Some reports analyze the addition of different oxides [8,9] and Zr [18][19][20].…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation